Odpowiedzi

2009-11-17T17:44:18+01:00
X² - 2x + x - 2 + x² - x + 2x - 2 = x⁴ - 4

5k² + 10kn + kn - 2n² - 4k² - kn = k² + 10kn - 2n²

4y² - 8y + 3y - 6 - 8y + 4y² = 8y² - 13y - 6
  • Użytkownik Zadane
2009-11-17T17:45:49+01:00
(x+1)(x-2)+(x+2)(x-1)=2x^2 - 4=2(x+2)(x-2)
(5k+n)(k-2n)-k(4k+n)=k^2 - 10kn - 2n^2
(4y+3)(y-2)-2y(4-2y)=8y^2 - 13y - 6
2009-11-17T17:50:09+01:00
(x+1)(x-2)+(x+2)(x-1)=x²+x-2x-2+x²-x+2x-2=2x²-4

(5k+n)(k-2n)-k(4k+n)=5k²-10kn+kn-2n²-4k²-kn=k²-2n²-10kn

(4y+3)(y-2)-2y(4-2y)=4y²-8y+3y-6-8y+4y²=
8y²-13y-6